2019
DOI: 10.1111/cyt.12789
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration cytology of extra‐salivary adenoid cystic carcinoma

Abstract: Introduction Adenoid cystic carcinoma (ACC) is a ubiquitous tumour which can occur in several sites of the human body. Commonly, it affects the salivary glands but also can rarely occur in various extra‐salivary locations. Aim To study the clinical and cytological features of extra‐salivary ACC on fine needle aspiration cytology. Methods In this paper, we included 27 patients with extra‐salivary ACC on fine needle aspiration cytology over a period of 5.5 years. The complete cytomorphological spectrum of extra‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Studies have revealed that ADCC-HGT has an increased tendency for lymph node metastasis, as high as 43–57%. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that ADCC-HGT has an increased tendency for lymph node metastasis, as high as 43–57%. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing investigation of molecular abnormalities underpinning ACC that may be responsible for carcinogenesis is critical to identifying and developing novel targeted therapies. As pertains to this review, ACC is focused on tumors arising within salivary tissue; however, it is important to recall that ACC tumors may also originate in the trachea, lung, and breast, among others [ 91 ]. Therefore, advances in the understanding of the molecular pathogenesis and associated possible targeted therapeutics for salivary ACC may offer insights into ACC elsewhere in the body.…”
Section: Discussionmentioning
confidence: 99%